2018
DOI: 10.1039/c8qo00801a
|View full text |Cite
|
Sign up to set email alerts
|

Base-promoted C–C bond cleavage for the synthesis of 2,3,4-trisubstituted pyrroles from N-propargyl β-enaminones

Abstract: The synthesis of 2,3,4-trisubstituted pyrroles via base-promoted C–C bond cleavage reaction of N-propargyl β-enaminones is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…7 Inspired by Lei's work, we questioned whether this open shell deacylative α-cupration mechanism might be translated to other transition metals, such as ruthenium, thereby allowing catalytic formation of alkyl Ru intermediates that can be captured by suitable coupling partners. In continuation of our research on C–C(CO) bond cleavage reactions,8 herein we disclose the first ruthenium-catalyzed deacylative annulation of 1,3-diones with sulfoxonium ylides (Scheme 1c). This method provides a practical and mild synthetic route to substituted furans,9 which are essential structural moieties in many biologically active compounds, natural products, and functional materials 10…”
Section: Introductionmentioning
confidence: 96%
“…7 Inspired by Lei's work, we questioned whether this open shell deacylative α-cupration mechanism might be translated to other transition metals, such as ruthenium, thereby allowing catalytic formation of alkyl Ru intermediates that can be captured by suitable coupling partners. In continuation of our research on C–C(CO) bond cleavage reactions,8 herein we disclose the first ruthenium-catalyzed deacylative annulation of 1,3-diones with sulfoxonium ylides (Scheme 1c). This method provides a practical and mild synthetic route to substituted furans,9 which are essential structural moieties in many biologically active compounds, natural products, and functional materials 10…”
Section: Introductionmentioning
confidence: 96%
“…Pioneering studies of Cacchi and Fabrizi and Saito and Hanzawa opened the way for the synthesis of type 1 and 2 pyrrole derivatives, respectively . Later, other research groups were also involved in the synthesis of such pyrrole derivatives . Besides, the Cheng research group reported a ring-closing carbonyl-allene metathesis reaction of N -propargyl β-enaminones, which provided 2,4-disubstituted pyrroles, called as type 3, via the intermediacy of dihydropyrrole-fused oxetanes (Scheme a, lower left) .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the works of Li and Ackermann, we questioned whether sulfoxonium ylides could be able to serve as both arenes and coupling partners in transition-metal-catalyzed C–H activation. As our ongoing interest in C–H activation and C–C cleavage, herein, we disclose a ruthenium­(II)-catalyzed dual C–H/C–C activation of sulfoxonium ylides for the synthesis of isocoumarins (Scheme d) …”
mentioning
confidence: 99%